Changes in the normal appearing brain tissue and cognitive impairment in multiple sclerosis. Issue 2 (1st February 2000) - Filippi, M; Tortorella, C; Rovaris, M; Bozzali, M; Possa, F; Sormani, M P; Iannucci, G; Comi, G
Abstract : OBJECTIVES: To assess ( a ) whether the changes in the normal appearing brain tissue (NABT), as revealed by magnetisation transfer (MT) histogram analysis, correlates with cognitive dysfunction in patients with multiple sclerosis and ( b ) the relative contribution of these changes by comparison with that of multiple sclerosis lesions visible on conventional MRI. METHODS: Dual echo, T1 weighted and MT scans of the brain were obtained in 12 patients with multiple sclerosis with cognitive impairment and in seven without cognitive impairment. Lesion loads were assessed from T2 and T1 weighted scans. To create MT histograms of the NABT, multiple sclerosis lesion outlines from dual echo scans were superimposed automatically and nulled out from the coregistered and scalp stripped MTR maps. Average lesion MT ratio (MTR) and brain size were also measured. RESULTS: T2 and T1 lesion loads were significantly higher and the average lesion MTR and brain size were significantly lower in the group of cognitively impaired patients. Patients with cognitive deficits also had significantly lower average MTR and peak location of the NABT histogram. Logistic regression analysis showed that 68% of the total variance was explained by average NABT-MTR alone. A multivariable regression model showed that NABT-MTR was the only factor that significantly correlated with cognitive impairment in these patients (p=0.001). CONCLUSIONS: The extent of abnormalities which go undetected when using conventional MRI is relevant in determining cognitive impairment in multiple sclerosis.